2020
DOI: 10.1177/0269216320981294
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and implementation of palliative care interventions for patients with chronic obstructive pulmonary disease: A systematic review

Abstract: Background: Although guidelines recommend palliative care for patients with chronic obstructive pulmonary disease, there is little evidence for the effectiveness of palliative care interventions for this patient group specifically. Aim: To describe the characteristics of palliative care interventions for patients with COPD and their informal caregivers and review the available evidence on effectiveness and implementation outcomes. Design: Systematic review and narrative synthesis (PROSPERO CRD42017079962). Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 64 publications
(422 reference statements)
1
18
1
Order By: Relevance
“…These barriers may be addressed by using transition points, such as hospitalisation, to screen for palliative care needs [ 13 ] and communication training to increase HCPs’ self-efficacy in discussing palliative care topics [ 14 ]. However, the empirical evidence on effective implementation strategies is still limited [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These barriers may be addressed by using transition points, such as hospitalisation, to screen for palliative care needs [ 13 ] and communication training to increase HCPs’ self-efficacy in discussing palliative care topics [ 14 ]. However, the empirical evidence on effective implementation strategies is still limited [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the need for palliative care has been widely acknowledged, little direction exists on successfully implementing it into routine COPD care [10]. The key barriers to timely initiating palliative care in COPD are the prognostic uncertainty due to the unpredictable illness trajectory and the lack of training of healthcare providers (HCPs) to discuss end-of-life topics [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our study, a recent systematic review found no effect of palliative care interventions on the quality of life of patients with COPD; effects on acute healthcare use were inconclusive. 9 It contrasts, however, with palliative care intervention studies in patients with cancer or chronic heart failure, in whom improved quality of life and less acute healthcare use was demonstrated. 6,17,18 Our findings could be explained in several ways.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…In a recent systematic review, only 4 out of 20 palliative care interventions in COPD had been evaluated in a powered controlled trial, and the effects on health outcomes remained inconclusive. 9 Furthermore, guidelines recommend palliative care delivery by 'generalists' (i.e. respiratory care providers) in the first place, and only specialist palliative care involvement in case of complexity, 10,11 but the integration of palliative care elements into routine COPD care (integrated palliative care), 12 has hardly been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Hemodialysis centers are a logical site for this care because their providers have preexisting relationships and regular interaction with patients, and they are uniquely qualified to address the role of dialysis treatment during goals of care discussions. However, there has been limited success in routinely implementing palliative care services for many serious illnesses, including kidney failure (10,11). Passive dissemination of best practices and reliance on individual provider continuing education are rarely sufficient to overcome multilevel barriers.…”
Section: Introductionmentioning
confidence: 99%